Study on Multiferroic Behaviour of Gd doped BiFeO3 Nanoparticles - Grewal, Inderdeep Kaur (My University, 2011)
Multiferroics defined as materials that exhibit more than one primary ferroic order parameter simultaneously (i.e. in a single phase). The four basic primary ferroic order parameters are ferromagnetism, ferroelectricity, ferroelasticity and ferrotoroidicity. Physics of multiferroics has possible applications in modern optics or in spintronics. They used as memory devices in which magnetic (ferroelectric) domains are controlled by an electric (magnetic) field and magnetooptical devices in which light polarization is controlled by an electric or a magnetic field. Nanosized rhombohedral structure with hexagonal phase of BiFeO3 nanoparticles doped with Gd were synthesized by solution combustion method using citric acid as fuel. The influence of size and Gd doping on structural, magnetic, ferroelectric and morphological properties have been investigated and tentatively discussed. The luminescence properties were studied by PL spectra, which confirm the presence of defect levels caused by Gd2+. Magnetic study showed that pure BiFeO3 was antiferromagnetic in nature as no saturation in M-H curve is observed on the other hand Gd doped BiFeO3 is ferromagnetic in nature. The study of ferroelectric behaviour of pure and Gd doped BiFeO3 observed that a weak ferroelectric loop was observed in case of pure and it increased by increasing the doping & 6% Gd doped BiFeO3 show elliptical P-E loop.
M.Sc. (Physics)
Keywords: Multiferroics; Ferroelasticity; Ferromagnetism; Nanoparticles